Longitudinal Associations Between e-Cigarette Use, Cigarette Smoking, Physical Activity, and Recreational Screen Time in Canadian Adolescents. Issue 7 (28th November 2021) - Irvine, Dylan S; McGarity-Shipley, Ellen; Lee, Eun-Young; Janssen, Ian; Leatherdale, Scott T
Abstract: Introduction: This study examined longitudinal associations between e-cigarette use, cigarette smoking, physical activity, and recreational screen time (ST) in a cohort of Canadian adolescents (ages 14–17 years; grades 9–12). Aims and Methods: Data from 5951 adolescents who participated in COMPASS Year 4 (2015–2016; baseline) and Year 6 (2017–2018; follow-up) were used. Exposures included e-cigarette use and cigarette smoking. Outcomes included cutpoints for moderate- to vigorous-physical activity (MVPA; ≥60 min/d), muscular strengthening exercises (MSE; ≥3 time/wk), participation in sport (SP; intramural or competitive), and recreational screen time (ST; ≤430 min/day). Generalized linear mixed models were performed. Results: e-Cigarette use (16.6% vs. 39.2%), cigarette smoking (0.9% vs. 4.7%), and dual use (0.8% vs. 4.1%) increased from baseline to follow-up. SP (70.8% vs. 61.3%) and the prevalence of meeting MVPA (49.8% vs. 42.1%) and MSE cutpoints (54.0% vs. 45.3%) decreased from baseline to follow-up. Recreational ST remained similar from baseline to follow-up. New e-cigarette use at follow-up was associated with maintenance of SP and meeting MVPA and MSE cutpoints, but also with increased ST. New cigarette smoking at follow-up was associated with maintaining high ST and low SP. Cigarette smoking at baseline and follow-up was associated with maintaining high ST, low MSE, and low SP. Cigarette smoking cessation at follow-up was associated with increasing MVPA and MSE, decreasing ST, and maintaining low SP. Conclusion: Given the clustering and co-occurring unhealthy behavioral patterns, intervention strategies to promote healthy lifestyles should take a holistic approach, by targeting multiple behavioral changes simultaneously. Implications: This investigation highlighted that, unhealthy behaviors, particularly e-cigarette use, cigarette smoking, and excessive use of screens, tend to co-occur among Canadian adolescents. Therefore, intervention strategies to promote healthy lifestyles should take a holistic approach, by targeting multiple behavioral changes simultaneously particularly in school and community settings. As an exception, new and stable e-cigarette use appears to co-occur with achieving sufficient levels of physical activity. Increasing awareness about the risk of e-cigarette use may target population groups that are physically and socially active (eg, athletes, sport teams).